(untitled) (Swiss Medical Weekly, 2011)
BACKGROUND: Sodium imbalance is common in-hospital electrolyte disturbance and is largely related to inequalities in water homeostasis. An important mechanism leading to dysnatraemic disorders is inadequately secreted plasma arginine vasopressin (AVP). Unfortunately, AVP measurement is cumbersome and not reliable. Copeptin is secreted in an equimolar ratio to AVP and is a promising marker in the differential diagnosis of hyponatraemia and possibly hypernatraemia in stable hospitalised patients. This study assessed copeptin concentrations in sick patients with serum sodium imbalance of different aetiology on admission to the emergency department. METHODS:This is a secondary analysis of three previous prospective studies including patients with lower respiratory tract infections (LRTI) and acute cerebrovascular events. Patients were classified into different aetiological groups of hyponatraemia and hypernatraemia based on gold standard diagnostic algorithms. Copeptin levels were compared between different volaemic states and different aetiologies, firstly within the different study populations and secondly in an overall pooled analysis using hierarchical regression analysis adjusted for age and gender. RESULTS:In LRTI, hyponatraemia was found in 10.6% (58/545) and hypernatraemia in 3.7% (20/545). For acute cerebrovascular events, the corresponding numbers were 4.3% (22/509) and 8.4% (43/509). In LRTI patients with hyponatraemia, copeptin levels were only lower in the subgroup of patients with gastrointestinal losses compared to the group of patients with renal failure (mean difference: –73.6 mmol/l, 95%CI –135.0, –12.3). For hypernatraemic patients and stoke patients with hypo- and hypernatraemia, no differences were observed. In the combined analysis, copeptin levels in the hyponatraemic population were higher in patients with a hypervolaemic volume state and in patients with heart failure and renal failure. When focusing on severity, copeptin levels increased with increasing severity of disease, as classified by the Pneumonia Severity Index (p <0.0001) or the National Institute of Health Stroke Scale Score (p <0.0001). CONCLUSION:Although limited by small sample size, this study found that plasma copeptin level appears to add very little information to the work up of sodium imbalance in this cohort of medical inpatients. It is likely that the non-osmotic “stress”-stimulus in acute hospitalised patients is a major confounder and overrules the osmotic stimulus.